MO023: Chronic kidney disease in HELIX syndrome. (3rd May 2022) - Prot-Bertoye, Caroline; Knebelmann, Bertrand; Bourrat, Emmanuelle; Hadj-Rabia, Smail; Vargas-Poussou, Rosa; Houillier, Pascal
Abstract: BACKGROUND AND AIMS: Rare genetic diseases affecting claudins (CLDN), integral proteins located at intercellular tight junction that determine the ionic selectivity and permeability of the paracellular pathway, highlighted the importance of paracellular transport in body homeostasis. Biallelic CLDN10B variants cause HELIX syndrome (MIM 617671), an autosomal recessive disorder encompassing Hypohidrosis, Electrolyte imbalance, Lacrymal gland dysfunction, Ichthyosis and Xerostomia. Cldn10b is expressed in the thick ascending limb of Henle's loop, which plays a key role in the tubular reabsorption of NaCl and magnesium. Whether HELIX syndrome is associated with a risk of early decline in GFR remains unclear. METHOD: We studied members of a family from Western Africa: three men born from consanguineous parents had HELIX syndrome. Median (min–max) of electrolyte concentrations is reported. Glomerular filtration rate (GFR) was calculated using creatinine-based CKD-EPI equation with correction factor for ethnic group. GFR was measured in two patients by the renal clearance of 99 Tc-DTPA. RESULTS: Biallelic missense variants in CLDN10 (c.408T > A p.Tyr136Ter in CLDN10A; c414T > A p.Tyr138Ter in CLDN10B) was identified in the three patients; both parents are heterozygous for this variant. Median (min–max) age was 19.8 (16.9–27.9) years. All patients had renal loss of NaCl with elevated plasma renin concentration, hypokaliemia [3.1 mmol/L (2.9–3.3)] with renal loss of potassium, hypermagnesemia [1.33 mmol/L (1.03–1.59)]. Median (min–max) estimated GFR was 72 (62–83) mL/min/1.73 m 2 . Measured GFR was 38.1 and 56.9 mL/min/1.73 m 2 . No significant proteinuria, microscopic hematuria or leukocyturia was found. CONCLUSION: Besides abnormalities in renal ion transport, a decrease in GFR can occur at an early age during the course of HELIX syndrome. CKD should be routinely screened and we suggest considering the measurement of GFR in these patients.